Productive performance in Italian Mediterranean buffaloes after partially replacing dietary starch with simple sugars - Roberta Matera; Gabriele di Vuolo; Giuseppina Pedota; Luca de Luise; Mariateresa Marra; Luca Borzacchiello; Ludovica Capoluongo; Gianluca Neglia (Revista Científica)
This study aimed to partially replace starch with simple sugars as a carbohydrate source in the diet of Italian Mediterranean buffaloes, substituting corn with molasses. Sixty lactating buffaloes located on a commercial farm in Caserta province were divided into two groups according to days in milk (DIM), parity, and milk yield (MY), recorded both in the previous two weeks and the previous lactation: Group C (Control; n=30; 48.7±4.1 DIM; average MY: 13.69±0.5 kg) and group T (Treated; n=30; 49.4±4.3 DIM; average MY: 13.65±0.5 kg). The two groups were maintained in separate paddocks throughout the study, which lasted 120 days. Two diets with the same dry matter (DM) content (16.5 kg) and nutritional characteristics on a DM basis (crude protein: 14.9%; NDF: 38.5%; Ash: 6.3%; NSC: 34.5%; energy density: 0.93 Milk Forage Units) were prepared. In the T diet, 1.7 kg of molasses was inserted, replacing corn meal and maize silage; thus, starch content was 19.8% and 17.2% in Diet C and T, respectively. The diets were administered twice/day in each group, and refusals were weighed and sampled daily to calculate average feed intake. Individual milk yield was recorded daily, and 15 days apart, an individual milk sample was collected for milk quality analysis (fat, protein, casein, lactose, urea, β- hydroxybutyrate [BHB] and fatty acids profile) through mid-infrared spectroscopy (Milkoscan FT6000®, Foss Electric). Data were analyzed through a mixed ANOVA. The average milk yield throughout the experimental period was 11.7±0.1 vs 12.2±0.1 kg, Group C and T, respectively. Buffaloes in Group C showed lower (p<0.01) fat content compared to Group T (8.33±0.1 vs. 8.58±0.1 in Group C and T, respectively) and similar protein and casein content (protein 4.41±0.0 vs 4.43±0.0 and casein 3.54±0.0 vs 3.57±0.0 in Group C and T, respectively). Interestingly, the urea concentration was higher in Group C compared to Group T (43.1±0.1 vs. 35.7±0.1, in Group C and T, respectively). In contrast, following simple sugars administration, BHB content was lower (0.22±0.1 vs 0.28±0.1 in Group C and T, respectively), probably because of higher butyric acid production. Regarding the acidic profile, only medium-chain fatty acids were lower in Group C vs. Group T (3,135±77 vs 3,379±79 in groups C and T, respectively). In conclusion, simple sugar administration in the diet of lactating buffaloes seems to increase milk yield and fat content, probably through an improvement in rumen efficiency.